Endoscopic endonasal resection of two rare cases of hemangiopericytomas invading the cavernous sinus and literature review - Wu, Yingxi; Gong, Li; Zhang, Yunze; Zheng, Min; Li, Junting; Xue, Yafei; Qu, Yan; Zhao, Tianzhi (Frontiers in Surgery, 2022)
Hemangiopericytomas (HPCs) invading the cavernous sinus (CS) are extremely rare invasive tumors that have a great propensity for local recurrence. To date, only eight cases have been reported in the literature. Owing to the abundant vascular supply of HPCs, intracavernous bleeding and important blood vessels and nerves passing through the CS, it is very difficult and challenging for neurosurgeons to completely resect HPCs. Here, we reported two cases of HPCs invading the CS and introduced their clinical manifestations, imaging findings, surgical approaches and histopathological features in detail. We implemented the surgery by the endoscopic transpterygoid transcavernous approach (ETPTCa) for the two patients, and one patient underwent gross total resection (GTR) and another underwent subtotal resection (STR) and postoperative stereotactic radiosurgery (SRS). The ETPTCa may serve as a viable option to facilitate HPCs resection. Radiotherapy is helpful in prolonging progression-free survival (PFS) following STR of the tumor.